Drought Resistance Indices for Screening of Potato (Solanum tuberosum L.) Genotypes - Zerihun Kebede Beyene; Firew Mekbib; Tesfaye Abebe; Asrat Asfaw (Turkish Journal of Agriculture: Food Science and Technology)
In breeding for drought tolerance, availability of precise, cheap and easy to apply selection tool is critical. The aim of the present study was to identify potential screening tools that are useful for selection of drought tolerant genotypes in potato and select drought resistant potato genotypes. The study assessed sixty clones arranged in a 10×6 alpha lattice design with two replicates in a managed stress experiment. Two irrigation treatments were applied: fully watered non-stress and terminal drought, where the irrigation water supply to the crop was withheld after 50 % flowering to induce post-flowering stress. Stress indices were calculated based on tuber yield of genotypes in both stressed and non-stressed conditions. Identification of drought tolerant genotypes based on a single index was less informative as different indices identified different genotypes as drought tolerant. Hence, to determine the most desirable drought tolerant clones rank sum of indices, correlation, and bi-plot display of the principal component analysis was employed. The indices modified stress tolerance index based on non-stressed yield, Men productivity, Geometric mean productivity, Stress tolerance index, Harmonic mean, modified stress tolerance index based on stressed yield and Yield index exhibited strong association with both yield under stressed and non-stressed yield. These indices discriminated drought tolerant genotypes with higher tuber yielding potential both under stress and non-stress conditions. Genotypes CIP-398180.612, CIP-397069.5, and CIP-304371.67 were identified as drought tolerant. These genotypes could be potentially grown both under drought prone and potential environments and these selection attributes could help to develop climate resilient potato varieties.